CREATION FOR A CADASTRAL INFORMATION SYSTEM FOR GONIN GORA LAYOUT IN CHIKUN LOCAL GOVERNMENT AREA OF KADUNA STATE, NIGERIA - Maikano, Samson; Maisamari, Isaac J.; Jayeola, Wilson A.; Dare, Akinrinshola; Okechalu, Samson O.; Bako, A. (FUDMA JOURNAL OF SCIENCES, 2020)
This study was carried out to determine the geographic information system (GIS) as a tool to examine spatial patterns of Gonin Gora layout in Chikun Local Government Area of Kaduna state. The study involves acquiring spatial and attribute data of the study area, creating relevant spatial layers containing vital information about the parcel within the area of study, designing an appropriate database using relational database model (RDBM) cadastral information system and demonstrating the usability of the cadastral information system (CIS) that was created by carrying out simple queries. The research procedure also involves data acquisition using Promark 3 GPS instrument, database design and spatial queries using ARCGIS (10.1). Three(3) single criteria queries were generated for parcel earmarked for religion worship, parcel set for educational purposes, parcels for commercial purposes were identified and multi- criteria seven (7) queries were generated. The database was created and it was successfully test run for cadastral information system as effective tool for quick retrieval of information
Keywords: Cadastral Information System, Geographic Information System, Database Creation.